Chemokine CCL2 prevents opioid-induced inhibition of nociceptive synaptic transmission in spinal cord dorsal horn - Mario Heles (BMC, 2021)
Abstract Background Opioid analgesics remain widely used for pain treatment despite the related serious side effects. Some of those, such as opioid tolerance and opioid-induced hyperalgesia may be at least partially due to modulation of opioid receptors (OR) function at nociceptive synapses in the spinal cord dorsal horn. It was suggested that increased release of different chemokines under pathological conditions may play a role in this process. The goal of this study was to investigate the crosstalk between the µOR, transient receptor potential vanilloid 1 (TRPV1) receptor and C–C motif ligand 2 (CCL2) chemokine and the involvement of spinal microglia in the modulation of opioid analgesia. Methods Patch-clamp recordings of miniature excitatory postsynaptic currents (mEPSCs) and dorsal root evoked currents (eEPSC) in spinal cord slices superficial dorsal horn neurons were used to evaluate the effect of µOR agonist [D-Ala2, N-Me-Phe4, Gly5-ol]-enkephalin (DAMGO), CCL2, TRPV1 antagonist SB366791 and minocycline. Paw withdrawal test to thermal stimuli was combined with intrathecal (i.t.) delivery of CCL2 and DAMGO to investigate the modulation in vivo. Results Application of DAMGO induced a rapid decrease of mEPSC frequency and eEPSC amplitude, followed by a delayed increase of the eESPC amplitude, which was prevented by SB366791. Chemokine CCL2 treatment significantly diminished all the DAMGO-induced changes. Minocycline treatment prevented the CCL2 effects on the DAMGO-induced eEPSC depression, while mEPSC changes were unaffected. In behavioral experiments, i.t. injection of CCL2 completely blocked DAMGO-induced thermal hypoalgesia and intraperitoneal pre-treatment with minocycline prevented the CCL2 effect. Conclusions Our results indicate that opioid-induced inhibition of the excitatory synaptic transmission could be severely attenuated by increased CCL2 levels most likely through a microglia activation-dependent mechanism. Delayed potentiation of neurotransmission after µOR activation is dependent on TRPV1 receptors activation. Targeting CCL2 and its receptors and TRPV1 receptors in combination with opioid therapy could significantly improve the analgesic properties of opioids, especially during pathological states.